Strangers in a Strange Land: Interaction Management on Internet Relay Chat - Rintel, Sean; Pittam, Jeffrey (Human Communication Research, 1997)
This article examines a set of interactions (logs) taken from the form of computer-mediated communication known as Internet Relay Chat (IRC). The authors were particularly concerned with the interaction management strategies adopted by the participants in the logs during the opening and closing phases of the interactions to develop interpersonal relationships and communicate socioemotional content, as illustrated by their attempts to initiate and/or close interactions with others using the medium. The article compares these strategies and their structure with those proposed for face-to-face (FTF) interactions and proposes an explanatory framework for the interaction management of opening and closing phases on IRC. It is suggested that interaction management in these phases of IRC logs is similar to that in casual group FTF interaction in terms of the general functions of the strategies used, but that the content, structure, and ordering of the strategies are subject to adaptation.
Rintel, E. S. & Pittam, J. 1997. Strangers in a strange land: Interaction management on Internet Relay Chat. Human Communication Research, 23, 507-534.